Peningkatan Keterampilan Berpikir Kritis dan Hasil Belajar Matematika Pada Siswa Kelas 4 Melalui Penerapan Model Problem Based Learning - Pamungkas, Dewi; Mawardi, Mawardi; Astuti, Suhandi (Universitas Pendidikan Ganesha, 2019)
This study aims to improve critical thinking skills and mathematics learning outcomes of 4th grade students at Middle Tingkir 02 Elementary School by applying the Problem Based Learning (PBL) learning model. The research carried out by Jhon Elliot's class action research type with four stages, namely planning, implementation, observation and reflection carried out in two cycles. Each cycle consists of three meetings. Data acquisition was obtained from instruments in the form of critical thinking skills assessment rubrics and tests for Mathematics learning outcomes. The subjects of this study were the 4th grade Tingkir Tengah Elementary School 02 as many as 35 students. The technical data analysis uses descriptive comparative techniques across cycles. The results showed: (1) there was an increase in students' critical thinking skills from the initial condition, cycle 1, and cycle 2. In the initial condition the critical thinking skills in the critical category were only 43%, in the first cycle 76%, and in the second cycle increased to 97%; (2) Mathematics learning outcomes of students also increase. In the initial conditions only 42% of students experienced completeness, in cycle 1 it increased to 51% of students who completed it, and in cycle 2 it increased to 68%.